Does Ethanolic Propolis Extract Affect Blood Clotting Parameters? Blood Clotting Effect of Propolis - Kolayli, Sevgi; Sahin, Huseyin; Malkoc, Meltem; Cakir, Hilal Ebru; Kara, Yakup; Bektas, Ozlen; Kaltalioglu, Kaan (Progress in Nutrition, 2022)
Ethanolic propolis extract (EPE) can be used as a food supplement since it is a rich source of phenolic acids and flavonoids. However, it is also suspected that a high level of phenolic substances may interact with blood-thinning drugs, such as warfarin. This preliminary study investigated the effect of warfarin combined with EPE on blood coagulation in rats. Prothrombin time (PT), international normalized ratio (INR), activated partial thromboplastin time (aPTT), and fibrinogen were measured in all experimental groups to determine blood coagulation effects. In addition, the propolis sample used in the study was analyzed in vitro. The total amounts of phenolic and flavonoid substances were 3884.30±18.20 mg GAE/100 mL and 1071.05±1.52 mg QU/100 mL, respectively. HPLC analysis identified rutin, caffeic acid phenyl ester (CAPE), and chrysin as major components. Moreover, while the EPE (200 mg/kg, bw) did not significantly affect coagulation parameters when used alone, it caused mild changes in combination with warfarin. In conclusion, the data obtained may be interpreted as evidence of a synergistic effect between the applied dose of EPE and warfarin, despite the expectation of a possible drug interaction.